Syndromic and Nonsyndromic Obesity: Underlying Genetic Causes in Humans. Issue 10 (9th June 2022) - Duis, Jessica; Butler, Merlin G.
Abstract: Growing evidence supports syndromic and nonsyndromic causes of obesity, including genome‐wide association studies, candidate gene analysis, advanced genetic technology using next‐generation sequencing (NGS), and identification of copy number variants. Identification of susceptibility genes impacts mechanistic understanding and informs precision medicine. The cause of obesity is heterogeneous with complex biological processes playing a role by controlling peptides involved in regulating appetite and food intake, cellular energy, and metabolism. Evidence for heritability shows genetic components contributing to 40%–70% of obesity. Monogenic causes and obesity‐related syndromes are discussed and illustrated as well as biological pathways, gene interactions, and factors contributing to the obesity phenotype. Over 550 obesity‐related single genes have been identified and summarized in tabular form with approximately 20% of these genes have been added to obesity gene panels for testing by commercially available laboratories. Early studies show that about 10% of patients with severe obesity using NGS testing have a pathogenic gene variant. Discussion to help characterize gene–gene interactions and disease mechanisms for early diagnosis, treatment, and risk factors contributing to disease is incorporated in this review. Abstract : Key identifying features, as well as biological pathways, gene interactions, and factors contributing to obesity, are discussed. Over 550 obesity–related single genes are identified in the literature and summarized in tabular form. Discussion to help characterize gene–gene interactions and disease mechanisms to allow for early diagnosis, treatment, and risk factors contributing to disease is incorporated in this review.